2020
DOI: 10.1002/smtd.201900689
|View full text |Cite
|
Sign up to set email alerts
|

Key Factors for Template‐Oriented Porous Titania Synthesis: Solvents and Catalysts

Abstract: Various types of titania nanostructures are synthesized with a polymer‐templated sol–gel method based on the amphiphilic diblock copolymer polystyrene‐b‐polyethylene oxide (PS‐b‐PEO) in combination with selective incorporation of the titania precursor titanium tetraisopropoxide. Custom tailoring of different types of titania morphologies is realized by changing the phase separation behavior of the PS‐b‐PEO template. Particularly, application of solvents from different categories is found to have a major impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…The synthesis and morphology control of TiO 2 templates are realized by a sol–gel synthesis approach according to previous work. , As illustrated by Figure a, the stock solutions are first prepared by dissolving the diblock copolymer polystyrene-block-poly­(ethylene oxide) (PS- b -PEO) into 1,4-dioxane, followed by adding titanium tetraisopropoxide (TTIP) as a titania precursor and 37% concentrated hydrochloric acid (HCl) as a poor solvent. Then, the TiO 2 thin films are obtained by spin coating the stock solutions on glass substrates, followed by a calcination process at 500 °C for 2 h in air.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis and morphology control of TiO 2 templates are realized by a sol–gel synthesis approach according to previous work. , As illustrated by Figure a, the stock solutions are first prepared by dissolving the diblock copolymer polystyrene-block-poly­(ethylene oxide) (PS- b -PEO) into 1,4-dioxane, followed by adding titanium tetraisopropoxide (TTIP) as a titania precursor and 37% concentrated hydrochloric acid (HCl) as a poor solvent. Then, the TiO 2 thin films are obtained by spin coating the stock solutions on glass substrates, followed by a calcination process at 500 °C for 2 h in air.…”
Section: Resultsmentioning
confidence: 99%
“…Among the different approaches of templating titania nanostructures, copolymerassisted sol-gel synthesis has been shown to provide a facile way toward a controlled morphology also for films. [19][20][21][22][23] Furthermore, solution processing based on copolymer-assisted sol-gel synthesis has shown high promise for economically producing nanostructured titania films via largescale deposition techniques, such as slot-die coating [24][25][26] and spray deposition. [27][28][29] However, the synthetic copolymer templating routine comes along with comparatively toxic, harmful, or flammable organic solvents as well as a low sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Related research in our group demonstrated the prominent influence of the PS-b-P 4 VP concentration on the ZnO morphology and the solvent effect during the polystyrene-block-polyethylene oxide (PS-b-PEO) templated TiO 2 and SnO 2 synthesis. [26,34,35] The formation of thermodynamically stable block polymer micelles is mainly governed by the following three contributions: The stretching degree of the core-forming polymer chains, the interfacial tension between the micelle core and the surrounding solvent, and the repulsive interactions among corona-forming chains. [25] The first two contributions can be affected by factors including copolymer composition and concentration, poor solvent content in the solution, and the preferential affinity of the common solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Related research in our group demonstrated the prominent influence of the PS‐b‐P 4 VP concentration on the ZnO morphology and the solvent effect during the polystyrene‐block‐polyethylene oxide (PS‐b‐PEO) templated TiO 2 and SnO 2 synthesis. [ 26,34,35 ]…”
Section: Introductionmentioning
confidence: 99%